Small Weirs, Big Effects: Disruption of Water Temperature Regimes with Hydrological Alteration in a Mediterranean Stream. (24th January 2015) - Bae, M.‐J.; Merciai, R.; Benejam, L.; Sabater, S.; García‐Berthou, E.
Abstract: The effects of hydrological alterations on thermal regimes due to small water provisioning schemes are poorly understood. We studied the alteration of thermal regimes in a Mediterranean stream, where a weir and a water abstraction have been previously shown to severely affect the flow regime (e.g. frequency and duration of drought) and fish assemblage. Compared to non‐impacted sites, the daily water temperature was more variable downstream of the weir, where water flow was reduced and drying occurred every summer. However, water temperature variation was smaller in a nearby downstream site dominated by effluents from a wastewater treatment plant. In addition, compared to all other sites, the times of the day to reach minimum and maximum water temperatures were markedly different in this site receiving the wastewater plant effluents and occurred earlier in the day in the site below the weir. The relationships between air and water temperatures were tight downstream but became looser and anomalous at the sites affected by water abstraction and effluent inputs. Overall, our results show that water temperature regimes in small streams are abruptly disrupted with water provisioning schemes with unknown consequences for aquatic organisms and ecosystems. Effects may be particularly stressful in Mediterranean‐climate streams, where water is scarce and hydrological alterations pervasive. Copyright © 2015 John Wiley & Sons, Ltd.